Expression of <g transform="matrix(.022,-0,0,-.022,.062,20.875)"><path id="x1D442" d="M745 361q0 -166 -116 -272t-291 -106q-136 0 -225.5 83t-89.5 218q0 161 115.5 272t288.5 111q137 0 227.5 -83t90.5 -223zM643 359q0 126 -56 199.5t-167 73.5q-130 0 -213.5 -104t-83.5 -246q0 -117 58 -190.5t165 -73.5q91 0 160.5 52t103 128.5t33.5 160.5z" /></g> <g transform="matrix(.016,-0,0,-.016,17.275,10.125)"><path id="x36" d="M137 343l67 33q37 17 63 17q79 0 129.5 -53t50.5 -131q0 -92 -58 -156.5t-147 -64.5t-147 68t-58 182q0 63 17 119t43 95.5t61.5 72t69 52t67.5 31.5q62 22 128 33l6 -32q-56 -11 -108 -35q-149 -71 -184 -231zM227 337q-47 0 -95 -27q-6 -23 -6 -70q0 -93 36 -155.5 t96 -62.5q53 0 78 45.5t25 105.5q0 68 -35 116t-99 48z" /></g> -Alkylguanine-DNA Alkyltransferase in Normal and Malignant Bladder Tissue of Egyptian Patients - Saad, Abir A.; Kassem, Heba Sh.; Povey, Andrew C.; Margison, Geoffrey P. (Journal of Nucleic Acids, 2010)
Bladder tumour tissues and corresponding uninvolved mucosa (normaltissue) of Egyptian bladder cancer patients were assessed forO6-alkylguanine-DNA-alkyltransferase (MGMT) activity by functionalassay of tissue extracts (36 paired samples), and distribution byimmunofluorescence (IF) microscopy of fixed material (24 pairedsamples). MGMT varied widely from 42–253 fmoles/mgprotein and from 3.2–40 fmoles/μg DNA in normal and 58–468 fmoles/mg protein and 2.5–49.5 fmoles/mg protein, inthe tumour tissues; only one tumour had undetectable activity. Pairwise comparison of MGMT activity in tumour and adjacent normaltissue showed no significant difference based on DNA content butwas 1.75-fold higher in tumour (P<.01) based on protein. There wasno effect of gender or bilharzia infection status. IF showed thatin tumours, both the mean percentage of positive nuclei (57.3± 20.3%) and mean integrated IF (5.47 ± 3.66) weresignificantly higher than those in uninvolved tissues (42.8± 13.5% P=.04) and (1.89 ± 1.42; P<.01), respectively. These observationssuggest that, overall, MGMT levels are increased during humanbladder carcinogenesis and that MGMT downregulation is not acommon feature of bladder cancers. Based on this, bladder cancerswould be expected to be relatively resistant to chemotherapy whichinvolved O6-guanine alkylating antitumour agents.